Pengaruh Model Pembelajaran Discovery Learning Berbantu Media Animasi Terhadap Hasil Belajar IPA Siswa - Nurmiati, Nurmiati; Fatimah, Waddi; Kamran, Muhammad; Cayati, Cayati (Universitas Hamzanwadi, 2023)
This research aimed to determine the effect of the discovery learning model by anomaly media on the learning outcomes of the fifth-grade students at SDN 010 Salutabang, Mamasa Regency. This research is quantitative research with the type of experimental research with the pre-experimental form of one group pretest-post-test design. The sampel in this study was 11 fifth-grade students consisting of 7 boys and 4 girls. The sampling technique in this study is saturated sampling. The research instruments used were observation sheets, learning achievement tests, and documentation. Data analysis used descriptive analysis and inferential statistical analysis with the help of the SPSS computer program. The results of this study indicate that the teacher’s ability in applying the discovery learning model assited by animation media gets on average value of 3.2, which means it well implemented. The learning outcomes of fifth-grade students are described from the results of the prerequisite test consisting of the normality test results pretest 0.162 ≥ 0,05 and post-test 0.620 ≥ 0,05 normally distributed, homogeneity test results 0.163 ≥ 0,05 which means homogeneous and the results from the hypothesis test 0.000 with Sig criteria (0.000) ≤ α (0,05). So, the results of this study indicate that there is an ifluence of the discovery learning model assisted by animation media on the learning outcomes of fifth-grade students at SDN 010 Salutabang, Mamasa Regency.